Contextual modulation of attention in human category learning - George, David N.; Kruschke, John K. (Learning & behavior, 2012)
In a category-learning experiment, we assessed whether participants were able to selectively attend to different components of a compound stimulus in two distinct contexts. The participants were presented with stimulus compounds for which they had to learn categorical labels. Each compound comprised one feature from each of two dimensions, and on different trials the compound was presented in two contexts, X and Y. In Context X, Dimension A was relevant to the solution of the categorization task and Dimension B was irrelevant, whereas in Context Y, Dimension A was irrelevant and Dimension B was relevant. The results of transfer tests to novel stimuli suggested that people learned to attend selectively to Dimension A in Context X and Dimension B in Context Y. These findings contribute to the growing body of evidence that people can learn to selectively attend to particular dimensions of stimuli dependent on the context in which the stimuli are presented. Furthermore, the findings demonstrate that context-dependent changes in attention transfer to other categorization tasks involving novel stimuli. © Psychonomic Society, Inc. 2011.
Batch 008. Output ID 43465. [NOT IN HARDCOPY YET 5/10/12]
Keywords: Experimental and Cognitive Psychology; Cognitive Neuroscience; Behavioral Neuroscience